Tracking platyhelminth parasite diversity from freshwater turtles in French Guiana: First report of Neopolystoma Price, 1939 (Monogenea: Polystomatidae) with the description of three new species - Du Preez, Louis H. (Parasit Vectors, 2017)
BACKGROUND: Polystomatid flatworms in chelonians are divided into three genera, i.e. Polystomoides Ward, 1917, Polystomoidella Price, 1939 and Neopolystoma Price, 1939, according to the number of haptoral hooks. Among the about 55 polystome species that are known to date from the 327 modern living chelonians, only four species of Polystomoides are currently recognised within the 45 South American freshwater turtles. METHODS: During 2012, several sites in the vicinity of the cities Cayenne and Kaw in French Guiana were investigated for freshwater turtles. Turtles were collected at six sites and the presence of polystomatid flatworms was assessed from the presence of polystome eggs released by infected specimens. RESULTS: Among the three turtle species that were collected, no polystomes were found in the gibba turtle Mesoclemmys gibba (Schweigger, 1812). The spot-legged turtle Rhinoclemmys punctularia (Daudin, 1801) was infected with two species of Neopolystoma Price, 1939, one in the conjunctival sacs and the other in the urinary bladder, while the scorpion mud turtle Kinosternon scorpioides (Linnaeus, 1766) was found to be infected with a single Neopolystoma species in the conjunctival sacs. These parasites could be distinguished from known species of Neopolystoma by a combination of morphological characteristics including body size, number and length of genital spines, shape and size of the testis. They were also differentiated at the molecular level using the cox1 gene marker. Based on morphological and genetic evidences, three new species are described herein, namely Neopolystoma cayensis n. sp. and Neopolystoma guianensis n. sp. from the bladder and the conjunctival sacs of R. punctularia, respectively, and Neopolystoma scorpioides n. sp. from the conjunctival sacs of K. scorpioides. However the monophyly of Polystomoides and Neopolystoma is still questioned regarding their phylogeny based on a dataset comprising four concatenated genes, namely, 18S, 28S and 12S rRNA genes and cox1. CONCLUSIONS: In addition to these being the first chelonian polystomes to be reported and described from French Guiana, they represent the first polystomes from the hosts K. scorpioides and R. punctularia and the first representatives of Neopolystoma from South America. Chelonian polystomes now require an in-depth morphological study to reconcile the taxonomy of the genera with species evolution.